Cloning, expression, and characterization of thermophilic L‐asparaginase from Thermococcus kodakarensis KOD1. (20th January 2014) - Hong, Sung‐Jun; Lee, Yun‐Ha; Khan, Abdur Rahim; Ullah, Ihsan; Lee, Changhee; Park, Choi Kyu; Shin, Jae‐Ho
<x xml:space="preserve">Abstract</x> The present study demonstrates cloning, expression, and characterization of hyperthermostable L‐asparaginase from Thermococcus kodakarensis KOD1 in Escherichia coli BLR(DE3). The recombinant 6× His‐tagged protein L‐asparaginase from T. kodakarensis (TkAsn), was purified to homogeneity by heat treatment followed by affinity chromatography using a nickel‐nitrilotriacetic acid (Ni‐NTA) column. The molecular mass of the purified enzyme was found to be approximately 37 kDa by sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS–PAGE). The enzymatic properties, such as optimum temperature and pH, were 90 °C and 8.0, respectively. Its appearent Km, Vmax, and Kcat values were 2.6 mM, 1121 µmol min−1 mg−1, and 694 S−1, respectively. The enzyme displayed high thermal stability at optimum temperature with an insignificant loss in enzymatic activity, retaining almost 90% of its activity over a time period of 32 h. The relative activity of the enzyme was significantly inhibited by the supplementation of Cu2+ and Ni2+ ions, while moderately inhibited by other ions. In contrast, Mg2+ ions enhanced the relative activity compared to the control. The acrylamide contents in baked dough were reduced to sixty percent after treatment with recombinant TkAsn as compared to the untreated control. Results of the present study revealed that the enzyme was highly active at broader range of temperatures and pH, which reflect the potential of recombinant TkAsn in the food processing industry. In addition, the high thermal stability of the enzyme may facilitates its handling, storage, and transportation.